Meta-analysis of the efficacy of digital therapies in children with attention-deficit hyperactivity disorder - He, Fan; Qi, Yanjie; Zhou, Yuanyue; Cao, Aihua; Yue, Xin; Fang, Shuanfeng; Zheng, Yi (Frontiers in Psychiatry, 2023)
The aim of this meta-analysis was to summarize the available evidence for the efficacy of digital therapeutics in children and adolescents of attention-deficit hyperactivity disorder (ADHD). We searched the MEDLINE, EMBASE, Cochrane Library (Cochrane Database of Systematic Reviews), and Web of Science (science and social science citation index) databases for relevant studies and used Stata 15.0 software to carry out the meta-analysis. A total of 31 studies involving 2189 participants (1681 boys and 508 girls) aged 4–17 years old were included in the final analysis. The meta-analysis results showed that digital interventions improved the symptoms of inattention with an effect value of -0.25 (95% confidence interval [CI] -0.40, -0.09) and decrease the continuous performance task (CPT) reaction time (effect, -0.40, 95% CI -0.73, -0.07) in ADHD patients. The score for impulsive hyperactivity was slightly decreased (effect, -0.13, 95% CI -0.28, 0.03). Moreover, executive function was improved (effect, 0.71, 95% CI 0.37, 1.04). The capability of working memory appeared to be increased (effect, 0.48, 95% CI 0.21, 0.76) between the two groups. Visual appraisal of the sensitivity analysis suggested the absence of heterogeneity, and no obvious publication bias was detected. Based on the existing literature evidence, we conclude that digital therapy can be a promising therapeutic strategy for ADHD patients.